Correction: Lin, Y., et al. Road Extraction from Very-High-Resolution Remote Sensing Images via a Nested SE-Deeplab Model. Remote Sens. 2020, 12, 2985 - Yeneng Lin; Dongyun Xu; Nan Wang; Zhou Shi; Qiuxiao Chen (Remote Sensing, 2021)
The authors wish to make the following correction to this paper [...]